2006
DOI: 10.1124/jpet.106.103853
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Alters Proliferation, Migration, and Differentiation of Human Fetal Brain-Derived Neural Precursor Cells

Abstract: Maternal use of cocaine during pregnancy is associated with sustained morphological brain abnormalities and sustained cognitive deficits in the offspring. Here, we use a cell culture model of highly enriched human fetal brain-derived neural precursor cells (NPCs) to assess the effects of cocaine treatment on their proliferation, migration, and differentiation. Our data show that cocaine treatment markedly inhibited the proliferation of NPCs, a phenomenon that was associated with cell cycle arrest, possibly bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 38 publications
(47 reference statements)
4
35
0
2
Order By: Relevance
“…An advantage of this model is that neural stem cells derived from neonatal rats may be used to evaluate the biologic effect and possible beneficial or toxic effects of drugs and some CNS (central nervous system)-acting nutrients, thus reducing the use of animal testing and making animal and human testing safer. The fate of NSCs in the brain may be regulated by growth factors, neurotransmitters and nutrients ( 11 ). The present study found that folate promotes proliferation and inhibits differentiation of NSCs.…”
Section: Discussionmentioning
confidence: 65%
“…An advantage of this model is that neural stem cells derived from neonatal rats may be used to evaluate the biologic effect and possible beneficial or toxic effects of drugs and some CNS (central nervous system)-acting nutrients, thus reducing the use of animal testing and making animal and human testing safer. The fate of NSCs in the brain may be regulated by growth factors, neurotransmitters and nutrients ( 11 ). The present study found that folate promotes proliferation and inhibits differentiation of NSCs.…”
Section: Discussionmentioning
confidence: 65%
“…Recent data in humans describe cocaine-induced alterations in p21 expression, as well as in the expression of CDKs, targets of p21, suggesting a relationship between these proteins and druginduced response (Hu et al, 2006;Zhou et al, 2011;Gelernter et al, 2014). To our knowledge, no studies exist, however, that directly examine the effect of p21 on cocaine-induced behaviors.…”
Section: Discussionmentioning
confidence: 92%
“…Although studies investigating the role of CDKs and their inhibitors in response to drugs of abuse are limited, published data illustrate a strong potential link between these proteins and cocaine-induced effects. For example, cocaine exposure has been shown to increase the expression of p21 in human neural precursor cells, correlating with decreased cell proliferation (Hu et al, 2006). In addition, Zhou et al (2011) recently reported alterations in CDKN1b (p27) and other CDK-associated proteins in the postmortem brain tissue of cocaine users.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, opiate drugs (and specifically the d-agonists) could promote survival signals in the brain through inhibition of FADD, which in turn is dependent on the activation of the antiapoptotic ERK1/2 signaling pathway (Garcia-Fuster et al, 2007), crucial for protection against Fas/FADD-mediated apoptosis (Holmstrom et al, 1999(Holmstrom et al, , 2000. Other experimental evidence has shown that cocaine alters proliferation, migration, and differentiation of human fetal brain-derived neural precursor cells (Hu et al, 2006). However, the potential effect of cocaine in inducing apoptosis of mature neurons is controversial.…”
Section: Regulation Of Fadd By Cocaine M-j García-fuster Et Almentioning
confidence: 99%